Epidemiological features of Hospital-acquired Pneumonia in an Internal Medicine Service from Guillermo Almenara Irigoyen Hospital in Lima, Peru - León-Chahua, César (2016)
Objetive: To determine the epidemiological features in patients with hospital-acquired pneumonia (HAP) in an Internal Medicine Service. Material and methods: A retrospective and descriptive study was carried out in Internal Medicine Service Nº5 from Guillermo Almenara Irigoyen National Hospital in 2015. Medical records of patients older than 15 years old were reviewed with the discharged diagnosis of HAP who meet the selection criteria. Results: Twenty six medical records were evaluated. The incidence rate of HAP was 2.37% and the mortality rate was 73.03%. The average age was 58.69 ± 12.49 years old. Patients older than 80 years old meant 42.31% of all of them. HAP was more frequent in male patients (65.38%). The average hospital stay was 62.53 days and 12 patients (46.15%) had more than sixty days of hospitalization. Among the intrinsic associated factors, the cerebrovascular disease was the most frequent illness, followed by the neoplastic disease with 23.07%. The most frequent extrinsic associated factors were the use of nasogastric tube and the stress ulcers prophylaxis with 84.61% each other, the endotracheal intubation with 53.84% and the mechanical ventilation with 50%. The isolated microorganisms were Acinetobacter baumannii (15.38%), Pseudomona aeruginosa (11.53%) and Staphilococcus aureus (3.84%). Conclusions: A high mortality rate was found in patients with HAP. Advanced age, comorbidities like cerebrovascular and neoplastic disease and the use of nasogastric tube and gastric secretor inhibitors were factors mostly found in HAP.